The Influence of Online Reviews, Influencer Credibility, Celebrity Endorsements on Purchasing Decisions for Scarlett Skincare Products - Nopri Muhammad Mandaki (Yayasan Darussalam Bengkulu, 2024)
The research in this thesis was carried out because more and more teenagers are using skincare to look beautiful and attract attention in the millennial era. Beauty is every woman's dream because it will make them more attractive. Skincare is important in supporting their beauty. The problem formulation for this research is how much influence Online Reviews, Influencer Credibility, and Celebrity Endorsement have on purchasing decisions for Scarlet Skincare products. This research is explanatory research which aims to explain the causal relationship between research variables through hypothesis testing. The method used is a survey method, namely data analysis from the population studied. The research results show that Online Reviews have a positive and significant effect on purchasing decisions, while Influencer Credibility has no significant effect and Celebrity Endorsments have a positive and significant effect.